(untitled) (Research, Society and Development, 2022)
The fourth industrial revolution, or Industry 4.0 is characterized as information technology enabling complete digital connectivity, bringing together modern human life’s physical, digital, and organic elements. In the competitive world of clothing, fashion and footwear, integrated technologies are constantly advancing, and the fashion industry needs to adapt to market standards. Given the above, this research aimed to search the literature in a bibliometric way on the evolution of the current situation of industry 4.0 fashion. In the present study, the research question that guided him is: What are the interventions of Industry 4.0 in the fashion industry? The bibliometric review is a contemporary view compared to the traditional bibliographic review, as the latter only allows an overview of specific subjects and is used as an argument for further research. A total of 16 articles demonstrated an overall performance of the technology in fashion, ranging from fabric production, eco-technology to reduce emissions and pollutants, technologies in production, distribution, marketing, and sales, in addition to having points for the sake of education. The application of IT in the structural organization of the form of production was the most highlighted by the studies and brought innovations in it, such as the application of 3D technology and intelligent and technological fabrics.